Model Remisi Ideal Sesuai dengan Prinsip Keadilan dan Transparansi - Nugraha, Farhanda; Wijayanti, Septi Nur (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2026)
Remission is a constitutional right of prisoners as stipulated in Article 14 paragraph (1) letter i of Law Number 12 of 1995 concerning Corrections. This right is not only interpreted as a reduction of sentence but also as an instrument of rehabilitation that reflects the state’s respect for human dignity. However, the granting of remission to corruption convicts often raises controversy, as corruption is regarded as an extraordinary crime. Government Regulation Number 99 of 2012 introduced the requirement of being a Justice Collaborator as a special condition, but this was annulled by the Constitutional Court through Decision Number 41/PUU-XIX/2021 on the grounds of being discriminatory and contrary to the principle of equality before the law. The decision restored remission requirements solely to the indicator of “good behavior,” yet the absence of clear parameters has created legal uncertainty and allowed room for subjectivity. This study employs a normative legal method with statutory, conceptual, and case approaches to analyze regulations, doctrines, court decisions, and practical cases of remission granted to corruption convicts. The results show that remission practices still fall short of the principles of objectivity, transparency, and accountability, and are not aligned with international standards such as the International Covenant on Civil and Political Rights (ICCPR) and the Nelson Mandela Rules. A remission assessment model based on measurable indicators, digital recording, and independent supervision is therefore required to ensure legal certainty and fairness. Such reformulation is expected to strengthen the anti-corruption agenda, enhance the legitimacy of the correctional system, and uphold the principles of good governance and the rule of law in Indonesia.